2014
DOI: 10.1021/jp509067u
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Infrared and Ultraviolet Matrix-Assisted Pulsed Laser Evaporation of Titanium Oxide/Graphene Oxide Composites: A Comparative Study

Abstract: Pure titanium dioxide (TiO 2 ) and graphene oxide (GO) as well as TiO 2 / GO composite structures were grown by matrix-assisted pulsed laser evaporation (MAPLE) in a controlled oxygen atmosphere. The MAPLE target dispersions were prepared using distilled water as solvent matrix, with TiO 2 nanoparticles (NPs) and GO platelets serving as host materials. Two laser sources, a free-running IR Er:YAG (λ = 2940 nm, τ fwhm ≅ 350 μs, ν = 10 Hz) and a UV KrF* excimer (λ = 248 nm, τ fwhm ≅ 25 ns, ν = 10 Hz) laser, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…16 Additionally, our previous results revealed that the lms' chemical composition and stoichiometry, and thus their functional, optical, electric, and catalytic properties can be easily adjusted through the MAPLE process parameters as the pressure as well as nature of the reactive gases in the irradiation chamber. [17][18][19][20] Moreover, in contracts to solvent-based chemical methods, laser technologies allow for the development of composites and multilayers bearing simultaneously various functionalities, as e.g. optical, catalytic, or magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…16 Additionally, our previous results revealed that the lms' chemical composition and stoichiometry, and thus their functional, optical, electric, and catalytic properties can be easily adjusted through the MAPLE process parameters as the pressure as well as nature of the reactive gases in the irradiation chamber. [17][18][19][20] Moreover, in contracts to solvent-based chemical methods, laser technologies allow for the development of composites and multilayers bearing simultaneously various functionalities, as e.g. optical, catalytic, or magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…MAPLE technique was applied during the last years for the immobilization of carbon nano-entities [20], SnO 2 [21] NPs, CdSe/ZnS core-shell quantum dots [22], TiO 2 nanorods [23], CNTs [24,25], GO platelets [26], and recently TiO 2 -rGO nanocomposites [27,28]. In this work TiO 2 and Au NPs, as well as GO platelets were used as base materials for the growth of TiO 2 , TiO 2 / Au / rGO, and nitrogen doped TiO 2 / Au / rGO composite thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to develop environmentfriendly methods for the preparation of these types of materials. Conversely, laser irradiation techniques have recently emerged as versatile, scalable, eco-friendly and easy ways for fabricating thin films composed of rGO-metal oxide nanostructures either by direct irradiation [20] or laser deposition [21,22] methods. Remarkably, the nature of ultraviolet pulsed laser radiation could lead to the attainment of new chemical pathways for the development of graphene-based nanocomposites with improved functionalities to be used in future devices.…”
Section: Introductionmentioning
confidence: 99%